High‐Pressure‐Sintering‐Induced Microstructural Engineering for an Ultimate Phonon Scattering of Thermoelectric Half‐Heusler Compounds. Issue 33 (8th July 2021) - He, Ran; Zhu, Taishan; Ying, Pingjun; Chen, Jie; Giebeler, Lars; Kühn, Uta; Grossman, Jeffrey C.; Wang, Yumei; Nielsch, Kornelius
Abstract: Thermal management is of vital importance in various modern technologies such as portable electronics, photovoltaics, and thermoelectric devices. Impeding phonon transport remains one of the most challenging tasks for improving the thermoelectric performance of certain materials such as half‐Heusler compounds. Herein, a significant reduction of lattice thermal conductivity (κL ) is achieved by applying a pressure of ≈1 GPa to sinter a broad range of half‐Heusler compounds. Contrasting with the common sintering pressure of less than 100 MPa, the gigapascal‐level pressure enables densification at a lower temperature, thus greatly modifying the structural characteristics for an intensified phonon scattering. A maximum κL reduction of ≈83% is realized for HfCoSb from 14 to 2.5 W m −1 K −1 at 300 K with more than 95% relative density. The realized low κL originates from a remarkable grain‐size refinement to below 100 nm together with the abundant in‐grain defects, as determined by microscopy investigations. This work uncovers the phonon transport properties of half‐Heusler compounds under unconventional microstructures, thus showing the potential of high‐pressure compaction in advancing the performance of thermoelectric materials. Abstract : High‐pressure sintering is applied for a broad range of half‐Heusler thermoelectric compounds to tailor their microstructures. Enriched concentrations of point defects and grain boundaries are found to drastically reduce the lattice thermal conductivity with a maximum reduction rate reaching 83%. These results suggest the great potential of high‐pressure sintering in advancing the performance of thermoelectric materials.